QUR’ANIC LANGUAGE ETHICS FROM THE PERSPECTIVE OF MAQĀṢIDĪ EXEGESIS: Quranic Solutions in the Use of Language for Teenagers - Wangsadanureja, Miftah; Edy, Sarwo; Saputera, Adha; Rabbani, Muhammad Aqil; bin Al-Muhsin, Muhammad Anas (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
Language constitutes a fundamental aspect of human life, essential for the clear reception and conveyance of information. Consequently, ethical linguistic conduct is imperative for effective human communication. The use of appropriate language fosters goodness, harmony, friendship (ukhuwah), and peace, whereas the use of offensive language can result in misunderstanding and engender hostility. This study aims to elucidate the ethics of language as presented in the Qur'an through the method of tafsīr maqāṣidī and its application in daily life. Employing a maqāṣidī exegetical approach combined with descriptive qualitative analysis within a sociolinguistic paradigm, this research involved a study of 64 dormitory students who practiced linguistic ethics. The findings indicate that the implementation of sound language ethics, both environmentally and individually, preserves four key principles of Maqāṣid al-Sharī'ah: ḥifẓ al-dīn (preservation of religion), ḥifẓ al-’aql (preservation of intellect), ḥifẓ al-nafs (preservation of life), and ḥifẓ al-bī'ah (preservation of the environment). Thus, the use of proper language is a core aspect of linguistic ethics, and its daily implementation positively impacts an individual's personality, thereby contributing to a harmonious, virtuous, and peaceful environment.